Model Indeks Kualitas Air Tanah sebagai Dasar Penentuan Alternatif Jenis Tanaman Pertanian pada Lahan Irigasi Air Tanah di Kabupaten Mojokerto - Hari Siswoyo; Pitojo Tri Juwono; Mohammad Taufiq (Department of Urban and Regional Planning, Diponegoro University, 2020)
The utilization of groundwater potential for irrigation has consequence for the high operational and maintenance costs of groundwater irrigation systems. One solution to these problems is the selection of high economic value crop types cultivated in groundwater irrigation lands. This study aims to determinate the alternative of types of agricultural crops that can be cultivated on groundwater irrigation land based on the quality of groundwater used as irrigation water based on the procedure: determination of groundwater quality index for irrigation, determination of types of agricultural crops based on criteria for tolerance to salt, adjustment of types of crop that have been determined with the criteria of high economic value crops, and adjustment to the types of crops that have been commonly cultivated by farmers in the local area. This procedure can be used as a solution to the absence of guidelines that can be used to determine alternative of types of agricultural plants on groundwater irrigation land. The results of this research showed the potential of ground water used as a source of irrigation water in the study site was dominated by groundwater with an index value of 70-85, where agricultural crops that could be recommended for planting were tolerant crops, moderately tolerant crops, and moderately sensitive crops to salt. The index value of groundwater quality for irrigation was mapped so obtained that zoning model of groundwater quality for irrigation and its suitability for the type of agricultural crops that can be cultivated.